Edukasi Dan Praktik Kebersihan Diri (Personal Hygiene) Saat Menstruasi Pada Remaja Putri Di Wilayah Lahan Kering - Serlie K.A. Littik; Noorce C. Berek; Christina R. Nayoan; Pius Weraman (CV. Multi Kreasi Media, 2026)
Personal hygiene is an essential aspect of health that should be maintained by everyone, including adolescent girls. Proper personal hygiene is particularly important during menstruation to prevent reproductive tract infections and other reproductive health problems. In addition, the regular monthly menstrual cycle in adolescent girls is closely associated with efforts to maintain stable hemoglobin levels and prevent anemia. However, many adolescent girls have insufficient knowledge regarding menstrual hygiene management and anemia prevention. Similar challenges related to inadequate knowledge and practices of personal hygiene, as well as poor adherence to iron and folic acid supplementation (IFAS), were identified among female students at SMP Negeri 1 Kupang Tengah, Kupang Regency, East Nusa Tenggara Province, Indonesia. This community service program aimed to improve knowledge and practices related to menstrual personal hygiene and to enhance motivation for regular IFAS consumption among adolescent girls at SMP Negeri 1 Kupang Tengah. The activities included health education sessions, group discussions, and demonstrations on menstrual personal hygiene; measurements of height and weight; hemoglobin screening; simultaneous distribution and supervised consumption of IFAS tablets; and the provision of hygiene kits containing sanitary pads and reusable water bottles. The results of the program demonstrated improved knowledge and strengthened commitment among the students to practice proper menstrual hygiene and to consume IFAS tablets regularly. Furthermore, teachers expressed their willingness to mentor the adolescent health peer group established following the program. The active participation of both students and teachers in this peer health group is expected to play a crucial role in ensuring the sustainability of the program outcomes.